2021
DOI: 10.6004/jnccn.2020.7678
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Utilization and End-of-Life Outcomes in Patients Receiving CAR T-Cell Therapy

Abstract: Background: CAR T-cell therapy has revolutionized the treatment of patients with hematologic malignancies, but it can result in prolonged hospitalizations and serious toxicities. However, data on the impact of CAR T-cell therapy on healthcare utilization and end-of-life (EoL) outcomes are lacking. Methods: We conducted a retrospective analysis of 236 patients who received CAR T-cell therapy at 2 tertiary care centers from February 2016 through December 2019. We abstracted healthcare utilization and EoL outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 37 publications
(45 reference statements)
0
25
0
Order By: Relevance
“…The ultimate goal was to create a general-purpose, open-source biomedical NLP tool that can be used for other applications; such tools can then be used to work on specific pathologies. This is the case of Johnson et al ( 52 ), who used ClinicalRegex 5 to examine social support in patients with aggressive hematologic malignancies. Khapre et al ( 53 ) and McDonald et al ( 54 ) similarly used General Architecture for Text Engineering (GATE), 6 an open-source NLP toolkit, to study symptoms in women with severe mental illness (i.e., psychotic and bipolar disorders) and in people with mood instability and/or sleep disturbance, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate goal was to create a general-purpose, open-source biomedical NLP tool that can be used for other applications; such tools can then be used to work on specific pathologies. This is the case of Johnson et al ( 52 ), who used ClinicalRegex 5 to examine social support in patients with aggressive hematologic malignancies. Khapre et al ( 53 ) and McDonald et al ( 54 ) similarly used General Architecture for Text Engineering (GATE), 6 an open-source NLP toolkit, to study symptoms in women with severe mental illness (i.e., psychotic and bipolar disorders) and in people with mood instability and/or sleep disturbance, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The ultimate goal was to create a general-purpose, open-source biomedical NLP tool that can be used for other applications; such tools can then be used to work on specific pathologies. This is the case of Johnson et al (52), who used ClinicalRegex 5 to examine social support in patients with aggressive hematologic malignancies. Khapre The above tools have highlighted two major problems in the development of NLP tools, namely:…”
Section: Natural Language Processing For Information Extractionmentioning
confidence: 99%
“…CAR-T cell therapy is an additional treatment modality with activity in indolent as well as aggressive HMs and data as to quality of life at the EOL with these treatments is only beginning to emerge. 32 Physical and psychological challenges are prominent in this group as well. Multiple myeloma is notorious for causing bone pain and spontaneous fractures 33 while lymphomas may behave as solid tumours compressing adjacent organs or nerves causing a variety of symptoms.…”
Section: Aggressive Hms -"The Rollercoaster"mentioning
confidence: 99%
“…Stem cell transplantation, a severely debilitating and dangerous intervention, can attain long term remission and even cure in a significant minority of patients and thus persists as a wild card treatment option in the eyes of both patients and clinicians. CAR‐T cell therapy is an additional treatment modality with activity in indolent as well as aggressive HMs and data as to quality of life at the EOL with these treatments is only beginning to emerge 32 …”
Section: Pc In Hmmentioning
confidence: 99%
“…Considering the potential side effects and the fact that not all patients will stay in remission after CAR-T therapy, many patients will need care in addition to the CAR-T treatment itself. A retrospective study examining post-CAR-T HCU in patients with lymphoma found that 28.1% of patients were admitted to the hospital at least once within 3 months of receiving CAR-T therapy, and 15.5% of patients had at least one intensive-care admission within 3 months of receiving therapy [ 39 ]. Another study examined HCU pre- and post-CAR-T administration in DLBCL patients and found that there were fewer ambulatory and emergency department visits in the months following CAR-T as compared to the months before; although patients are returning to the hospital, HCU-related costs were significantly lower after treatment [ 40 ].…”
Section: Clinical Outcomesmentioning
confidence: 99%